Simulation of Virtual Prototype and Research of Transmission Accuracy for RV Reducer - Liu Huaming; Qin Xunpeng; Huang Jinjing; Wu Rui (Jixie chuandong)
The parametric model of the cycloidal gear is established by using the equation of the trochoidal profiles on the platform of UG,and the 3D model of the RV reducer is established,then the virtual prototype model of RV reducer is obtained by importing the 3D model into ADAMS software. The rotational speed of the output shaft,the crank shaft and the cycloidal gear is obtained by simulation and the meshing frequency of the cycloidal gear and the pin tooth is investigated,the simulation results are in agreement with the theoretical results of the 9. 73 Hz,and the rationality and accuracy of the virtual prototype model is verified. The 8 groups virtual prototype models with consideration of the error are given,the simulation results show that the error of the pin radius,the modification of the cycloidal gear tooth profile and the error of the center circle of the pin have a great influence on the transmission accuracy. The research conclusions provide a theoretical basis for the design of RV reducer.